Strategic valuation of smart grid technology options in distribution networks - Konstantelos,I; Giannelos,S; Strbac,G (IEEE Transactions on Power Systems, 2016)
The increasing penetration of renewabledistributed generation (DG) sources in distribution networks canlead to violations of network constraints. Thus, significantnetwork reinforcements may be required to ensure that DGoutput is not constrained. However, the uncertainty around themagnitude, location and timing of future DG capacity rendersplanners unable to take fully-informed decisions and integrateDG at a minimum cost. In this paper we propose a novelstochastic planning model that considers investment inconventional assets as well as smart grid assets such as demandsideresponse, coordinated voltage control and soft open points(SOPs). The model also considers the possibility of active powergeneration curtailment of the DG units. A node-variableformulation has been adopted to relieve the substantialcomputational burden of the resulting mixed integer non-linearprogramming (MINLP) problem. A case study shows that smarttechnologies can possess significant strategic value due to theirinherent flexibility in dealing with different system evolutiontrajectories. This latent benefit remains undetected undertraditional deterministic planning approaches which may hinderthe transition to the smart grid.